Bridging The Gap Between The Past And The Present: A Reconsideration Of Mosque Architectural Elements - Asfour, Omar S (Journal of Islamic Architecture, 2016)
Mosques are among the most important building types for any community, where Muslims gather for their prayers and social activities. Mosque architecture has developed over history and faced several dramatic changes. This raises a question regarding the reality of mosque architecture and how it should look like today. This paper discusses this issue through a historical overview and some critical observations. Firstly, the paper discusses the historical functional role of mosque basic elements. Validity of these elements within the context of modern architecture has been argued considering the contemporary inputs that have a significant impact on mosque architecture. Several cases are presented and discussed in this regard. The study concluded that there is a great symbolic and spiritual value of these elements that should be maintained. The analysis carried out of several contemporary cases revealed that there is a wide margin to revive and reintroduce these elements in the light of the modern architectural trends. In addition to their functional roles, mosque architectural elements could be used as identity elements of the Islamic city, microclimatic modifiers, and linking tools between the past and the present.